(untitled) (Research, Society and Development, 2023)
Due to the periodic reemergence of epidemic outbreaks of yellow fever, the present research project aimed to investigate the relationship between the vaccination coverage and the morbidity and mortality rates of yellow fever in Brazil. This is an ecological study with a quantitative approach in Brazil, based on the quantitative survey of the number of hospitalizations, deaths, and yellow fever vaccination coverage rate, in the period delimited by 2016 and 2020, in DATASUS. The data were analyzed using descriptive statistics and graphical representation using the Microsoft Excel 2016 program, as well as maps in the Tabwin/DATASUS software. An increase in hospitalizations and deaths was observed at the expense of the low vaccination coverage rate, especially in the Southeast. In view of the findings, reflection emerges on effective strategies for increasing vaccination coverage as a prophylactic measure, aiming to control cases of yellow fever, to avoid hospitalizations and deaths from the disease, especially in non-endemic areas.